Determinants of Customer Satisfaction in Mobile Banking Services in Azerbaijan - Mammadov, Fuad (ADA University, 2021)
The quality of the products and services they offer has an important place in meeting the customer demands of service enterprises. One of the most important building blocks that will enable a business to stand out from the competition is to provide better quality services and to provide trust. It is extremely important to ensure customer satisfaction as a result of the quality of services offered within the banking sector. Today, mobile banking, which is one of the alternative distribution tools in electronic banking, has gained an important place among banking transactions by showing a rapid development. The aim of this thesis study is to reveal the relationship and the effect between the variables that enable customers using mobile banking to be satisfied with the service they receive. It is also to determine whether customer satisfaction in mobile banking services differs according to some demographic variables. For this purpose, a research was conducted on the customers of a private bank aged 15-54 using mobile banking, living in Baku. 399 people participated in the research. The data needed in the research were collected using the questionnaire technique, which is one of the quantitative research methods. The obtained data were analyzed in SPSS 25.0 program. According to the results of the study, the most important factors affecting customer satisfaction in mobile banking are respectively ease of use, support given to the service provided, service security, service performance, persuasion that the transactions are done correctly, the content of the service offered and the efficiency of the transactions. It has been found that the variables of education level, age level, income level, duration of use and frequency of use are effective on customer satisfaction in mobile banking.
Keywords: Mobile banking; Customer satisfaction -- Banking industry; Electronic banking -- User studies; Business